Power Efficient Group Communication in Small Cell Networks - Christos Bouras; Antonios Alexiou; Dimitrios Billios (Fourth International Conference on Selected Topics in Mobile & Wireless Networking (MoWNET' 2014), 2014)
Small Cell Networks (SCNs) constitute a new promising way for increasing coverage, boosting data rates and lowering capital and operating expenditures (CAPEX and OPEX) of today’s mobile networks. In this paper, we deal with the problem of efficient power control in SCNs. We propose and evaluate an efficient power control mechanism for SCNs, which efficiently controls the available power resources of the network, while on the other hand guarantees home users’ Quality of Service. We introduce the methodology of Priority Grouping, in which home users in the topology, are assigned to one of a number of predefined groups, with different priorities, in terms of traffic requirements. Furthermore, the mechanism dynamically updates the power setting of home base stations, based on the topology of the macro and home users in real time.